2009
DOI: 10.1007/s00402-008-0810-8
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic suture anchor repair of posterior root attachment injury in medial meniscus: technical note

Abstract: A root attachment injury (root tear) of the meniscus can abolish the ability of the meniscus to bear hoop stress and predispose to increase articular contact stress which contribute to femorotibial degenerative changes. A pull out suture technique to repair the root tear has been described, but the procedure making the tibial tunnel may be difficult and troublesome. This article describes a repair technique using a suture anchor and posterior trans-septal portal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
39
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 10 publications
0
39
0
1
Order By: Relevance
“…This requires a posterior portal and a curved suture passing device that can be difficult to manipulate within the knee. 6,7 We present a technique for posterior medial meniscus root repair using 3 sutures (1 leader, 2 cinch), standard arthroscopy portals, and transtibial fixation.…”
mentioning
confidence: 99%
“…This requires a posterior portal and a curved suture passing device that can be difficult to manipulate within the knee. 6,7 We present a technique for posterior medial meniscus root repair using 3 sutures (1 leader, 2 cinch), standard arthroscopy portals, and transtibial fixation.…”
mentioning
confidence: 99%
“…Suture anchor 3,4 and pull-through suture repair 1,5,6 techniques have been reported with satisfactory results. These techniques, to date, have all required use of a posterior portal 1,3-5 and/or a curved sutureshuttling device, 1,5,6 both of which can be technically challenging.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, prior root repair techniques have used varying suture configurations: simple, 4,6 double simple, 3 and single-locking loop. 1 A recent biomechanical study showed a double-locking loop configuration, as described in our technique, to have higher maximum load to failure than other configurations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahn et al 9 have shown the technique of the pullout suture using a trans-septal portal with the suturing done using a crescent-shaped suture hook from the posteromedial portal. Kim et al 10 have described the technique used to repair the medial meniscal root using a suture anchor. One study has shown superior biomechanical properties of the suture anchor repair technique when compared with the transtibial pullout repair.…”
Section: Discussionmentioning
confidence: 99%